2022
DOI: 10.1002/anie.202204781
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I) α‐Trifluoromethyl Carbenes: Synthesis, Characterization and Reactivity Studies

Abstract: Aryl trifluoromethyl diazomethanes 2-R (R = Ph, OMe, CF 3 ) are readily decomposed by the (o-carboranyl)diphosphine gold(I) complex 1. The resulting α-CF 3 substituted carbene complexes 3-R have been characterized by multi-nuclear NMR spectroscopy as well as X-ray crystallography (for 3-Ph). The bonding situation was thoroughly assessed by computational means, showing stabilization of the electrophilic carbene center by π-donation from the aryl substituent and backdonation from Au, as enhanced by the chelating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…Under the optimized conditions, the scope of the benzylic CÀ H insertions was examined using a variety of α-CF 3 -amine hydrochlorides, which correspond to products 2-37 (Table 1). The substrates with aryl group having different electronic properties (2, 5-11), substitution patterns, and shapes (12)(13)(14)(15)(16) are well-accommodated with the catalyst, affording the desired products in 85-95 % yield with up to 96 : 4 enantioselectivities, up to 98 : 2 site-selectivities and > 99 : 1 diastereoselectivities. For the substituents on the The E/Z ratios, regioisomeric ratios (r.r.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the optimized conditions, the scope of the benzylic CÀ H insertions was examined using a variety of α-CF 3 -amine hydrochlorides, which correspond to products 2-37 (Table 1). The substrates with aryl group having different electronic properties (2, 5-11), substitution patterns, and shapes (12)(13)(14)(15)(16) are well-accommodated with the catalyst, affording the desired products in 85-95 % yield with up to 96 : 4 enantioselectivities, up to 98 : 2 site-selectivities and > 99 : 1 diastereoselectivities. For the substituents on the The E/Z ratios, regioisomeric ratios (r.r.)…”
Section: Resultsmentioning
confidence: 99%
“…Ruthenium α-CF 3 -α-alkyl carbene complexes containing reactive 1,2-H and 1,5-H were also observed. [14]…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the rational design of ligands has played a crucial role in the development of new transformations at gold, such as oxidative addition, migratory insertion, or β-hydrogen elimination, which has opened the door for the discovery of new catalytic transformations. Additionally, the development of new ligands has permitted the isolation of unusual gold species that had been elusive for years and that have been considered as catalytic intermediates in the aforementioned transformations . Our group has contributed to this area by using sterically demanding phosphine ligands to access unusual Au­(I) structures such as hydrocarbyl-bridged cationic digold complexes and dicoordinate gold­(I) ethylene species, together with their use as FLP constituents …”
Section: Introductionmentioning
confidence: 99%
“…The HOMO/LUMO energy gap (2.64 eV) is comparable to those found in disubstituted (P^P)AuC(R)(R′) + carbenes (2.34–2.58 eV). 6 In addition, a Natural Localized Molecular Orbital (NLMO) associated to the Au → C carb backdonation evidences non-negligible mixing of the 2p π (C carb ) orbital with the d(Au)-centered orbital (9.1% C carb ), in line with some AuC carb π-bonding. 9…”
mentioning
confidence: 96%
“…Over the past few years, our group has demonstrated that ( o -carboranyl)-diphosphines are very efficient in enhancing backdonation from gold (thanks to P^P chelation) and stabilizing disubstituted gold( i ) carbenes. 2 c ,6 In this work, we envisioned to combine this approach with kinetic stabilization by a sterically demanding substituent. Hereafter, we report our first results along this line.…”
mentioning
confidence: 99%